Outdoor Performance of Fluidic Glass–Glass Laminate Windows for Building Integration - Heiz, Benjamin P.; Pan, Zhiwen; Wondraczek, Lothar (Energy Technology, 2019)
Fluidic windows enable the implementation of liquids in building envelopes. Such liquids may act as a heat reservoir and exchange medium or provide additional functionality to the building skin. Here, outdoor operations of double-glazed windows which include a transparent capillary panel as one of the glazings are reported. The capillary devices were used as heat exchangers by which water circulates across the window surface. A mobile demonstration facility is built, which uses 1.6 m 2 of active window surface for thermal input to a test room of 9 m 3 . Outdoor operations are conducted over multiple weeks in winter and summer seasons to demonstrate hydronic heating and cooling, respectively, by varying the inlet temperature and the flow rate of the circulating liquid. For heating operations at an outdoor air temperature of −5 °C, an overall heat transfer coefficient of 22 W m −2 K −1 is demonstrated. Using the same system for cooling with southeast façade orientation at an average solar irradiance of 800 W m −2 enables significant reduction of peak and average room temperature. In comparison to conventional heating, ventilation and air-conditioning technology, a significant reduction of the applied temperature gradient and air circulation rates is achieved.
CRIS-Team Scopus Importer:2023-04-20
Keywords: cooling; energy-efficient buildings; fluidic windows; glass; heating; smart windows